Effects of Astragalus polysaccharides on memory impairment in a diabetic rat model - Dun C; Liu J; Qiu F; Wu X; Wang Y; Zhao Y; Gu P (Neuropsychiatric Disease and Treatment)
Changping Dun,1 Junqian Liu,1 Fucheng Qiu,1 Xueda Wu,2 Yakun Wang,3 Yongyan Zhao,4 Ping Gu1 1Department of Neurology, the First Hospital of Hebei Medical University, 2Department of Cardiac Surgery, the Second Hospital of Hebei Medical University, 3Department of Endocrinology, the Fourth Hospital of Hebei Medical University, Shijiazhuang, 4Department of Nursing, Maternal and Child Health Hospital of Tangshan City, Tangshan, People’s Republic of China Objective: Astragalus polysaccharides (APS) are active constituents of Astragalus membranaceus. In this study, we aimed to investigate the effects of APS on memory impairment in a diabetic rat model and their mechanisms. Methods: A diabetic model was established in 50 male Wistar rats with streptozotocin intraperitoneal injection. A blood glucose level higher than 16.7 mmol/L obtained 72 hours after the injection was regarded as a successful diabetic model. The modeled rats were divided into model group, high, medium, and low doses of APS, and piracetam groups (positive control). A group of ten rats without streptozotocin-induced diabetes were used as a normal control. After respective consecutive 8-week treatments, the levels of blood fasting plasma glucose, insulin, hemoglobin A1c, memory performance, hippocampal malondialdehyde, and superoxide dismutase were determined. Results: After the 8-week APS treatment, serum fasting plasma glucose, hemoglobin A1c, and insulin levels were decreased compared with those of the model group (P<0.05). Importantly, memory impairment in the diabetic model was reversed by APS treatments. In addition, hippocampal malondialdehyde concentration was lowered, whereas that of superoxide dismutase was higher after APS treatments. Conclusion: APS are important active components responsible for memory improvement in rats with streptozotocin-induced diabetes. The potential mechanism of action is associated with the effects of APS on glucose and lipid metabolism, and antioxidative and insulin resistance. APS are constituents of A. membranaceus that are potential candidate therapeutic agents for the treatment of memory deficit in diabetes. Keywords: diabetic, Astragalus polysaccharides, memory impairment, MDA, SOD